Brain natriuretic peptide in pulmonary arterial hypertension: biomarker and potential therapeutic agent - Casserly, Brian (Dove Medical Press, 2009)
B-type natriuretic peptide (BNP) is a member of the natriuretic peptide family, a group of widely distributed, but evolutionarily conserved, polypeptide mediators that exert myriad cardiovascular effects. BNP is a potent vasodilator with mitogenic, hypertrophic and pro-inflammatory properties that is upregulated in pulmonary hypertensive diseases. Circulating levels of BNP correlate with mean pulmonary arterial pressure (mPAP) and pulmonary vascular resistance (PVR) in patients with pulmonary arterial hypertension (PAH). Elevated plasma BNP levels are associated with increased mortality in patients with PAH and a fall in BNP levels after therapy is associated with improved survival. These findings have important clinical implications in that a noninvasive blood test may be used to identify PAH patients at high-risk of decompensation and to guide pulmonary vasodilator therapy. BNP also has several biologic effects that could be beneficial to patients with PAH. However, lack of a convenient method for achieving sustained increases in circulating BNP levels has impeded the development of BNP as a therapy for treating pulmonary hypertension. New technologies that allow transdermal or oral administration of the natriuretic peptides have the potential to greatly accelerate research into therapeutic use of BNP for cor pulmonale and pulmonary vascular diseases. This review will examine the basic science and clinical research that has led to our understanding of the role of BNP in cardiovascular physiology, its use as a biomarker of right ventricular function and its therapeutic potential for managing patients with pulmonary vascular disease.